(untitled) (New York, 2006)
This is an excellent update on the whole field of prenatal diagnosis and care.. The book is comprehensive, inclusive, well presented, and well illustrated. It will serve as a definitive resource. 4 Stars!"--Doody's Review Service. (Doody's )
Keywords: Prenatal diagnosis.,Chuẩn đoán trước khi sinh